Southern Thailand: The origins of violence - Felix Heiduk; Kay Moeller (Stiftung Wissenschaft und Politik (SWP), 2004)
The assaults launched by Muslim youths on 28 April 2004 against police posts and military installations in three Thai provinces marks the climax, for the time being, of the unrest that has been mounting in the south of the kingdom since early January. Thus far, there are few indications of links with international terrorism. Should the situation escalate further, however, the existence of such links cannot be ruled out.(SWP Comments / SWP)
Keywords: 320